Lewis Acid Mediated Synthesis of 4-Aminoquinoline Derivatives from 2-Aminobenzonitriles and Activated Alkynes via Aza-Michael and Annulation Reactions - Porashar, Bikoshita; Saikia, Anil K. (Synthesis, 2024)
An efficient methodology for the synthesis of highly diverse 4-aminoquinoline derivatives from activated alkynes and 2-aminobenzonitriles mediated by Lewis acid is described. The reaction proceeds via sequential aza-Michael addition/intramolecular annulation to afford highly substituted 4-aminoquinolines in good yields. The reaction is operationally simple and has high atom-economy with broad substrate scope. The post synthetic application of the reaction provides 4H-benzo[de][1,6]naphthyridines.
Keywords: N-heterocycles; 4-aminoquinoline; 2-aminobenzonitrile; propynoate; ynone; aza-Michael; benzannulation